Examination and optical correction of the vision system following the procedure of cataract removal - Dębińska, Emilia; Styszyński, Andrzej; Naskręcki, Ryszard (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
The main goal of this thesis was a comprehensive assessment of the condition of the vision system following cataract surgery and implantation of posterior chamber artificial lens and assessment of the postoperative astigmatism, considering the dynamics of reduction of the postoperative astigmatism in the early postoperative period (3 months after the surgery). Also, the assessment of binocular vision of the operated patients was carried out. The results obtained were related to the currently used procedure methods, i.e., phacoemulsification and extracapsular cataract removal. The thesis is realized in cooperation with the Ophthalmic Department of the Province Hospital in Poznañ (Szpital Wojewódzki w Poznaniu), Poland.
Optica Applicata, Vol. 36, 2006, nr 4, s. 601-607
Keywords: optyka; physiological optics; optometry; binocular vision; stereopsy; cataract